Mortes violentas relacionadas ao consumo de drogas psicoativas na região metropolitana de Belém: estudo prospectivo no período de janeiro a dezembro de 2011 - (:unkn) unknown (Universidade Federal do Amazonas - Universidade Federal do Pará, 2012)
This is a cross-sectional study, which aimed to analyze and understand the correlation between violent deaths and the presence of psychoactive drugs in fatal victims, considering parameters such as sex, qualification, marital status and age. We analyzed 449 samples of blood and urine from the autopsied body at the Forensic Institute in Belém do Pará, in the period from January to December 2011. Analyses of psychoactive drugs were made by the techniques of gas chromatography, thin layer chromatography and gas liquid chromatography. The results showed that among violent deaths, particularly homicides, most individuals showed a positive result for drugs (69.18%), followed by suicides (66.67%) and accidents in general (49.48%), with higher prevalence of associated consumption of alcohol and cocaine in the age groups 20-34 years old of both sexes. Homicides were predominantly in male (76.30%), followed by accidents (19.80%) and suicides (3.90%). In females, (46.20%) predominated murder cases, followed by accidents in general (41.00%) and suicides (12.80%). Regarding marital status, the study found that in male and female gender, there was a prevalence of singles in almost all age groups, except for males aged 50 or more, where singles were equal to married men. In the professional qualification variant, the student profession predominated in the age group 12-19 years old in both sexes. However, in females in all the other age groups, there was the prevalence of housewives. Considering male subjects, there was a predominance of the profession of bricklayers, except in the range of 50 years old or more, where the number of retired employees prevailed. These data suggest that psychoactive drugs are highly related to violent deaths, particularly in homicides involving young male subjects
Keywords: Drogas ilícitas; Drogas psicoativas; Suicídio; Homicídio; CIÊNCIAS DA SAÚDE: SAÚDE COLETIVA